2017
DOI: 10.1002/slct.201701687
|View full text |Cite
|
Sign up to set email alerts
|

Improved Electrochemical Oxidation of Polyalcohols in Alkaline Media on Palladium-Nickel Catalysts

Abstract: Palladium is an efficient monoatomic catalyst for the electrochemical oxidation of polyalcohols in alkaline media, yet the oxidation rate is still slow compared to other smaller molecules. In order to improve the oxidation rate, Ni was mixed with Pd for synthesis of PdNi/C nanoparticles. The oxidation rates of ethylene glycol (EG), propylene glycol (PG), and glycerol (G) on Pd/C were compared to the oxidation rates on Pd16Ni84/C, Pd53Ni47/C, and Pd68Ni32/C. The oxidation rate of PG was enhanced by the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Researchers have revealed that amphoteric metals (e. g. Al and Ga) have similar effects as their 3p orbitals can mix with the Pt(5d) orbitals [160] . This downshift can also be induced by ad‐atoms with a different work function, because they can induce electron transfer from substrate metals (e. g. Pt) to them, lowering of density of states near Fermi level of the substrate metals to reach an equilibrium between two metals, [2,161] and this electron transfer can prevent the oxidation of substrate metals [40] . In addition, the lattice strain generated by ad‐atoms can also downshift the d‐band center of the metal they modify, and the effectiveness of lattice strain depends on the difference between their lattice parameters [162] .…”
Section: Electrocatalysts For Enhanced Efficiency and Selectivity Of mentioning
confidence: 99%
“…Researchers have revealed that amphoteric metals (e. g. Al and Ga) have similar effects as their 3p orbitals can mix with the Pt(5d) orbitals [160] . This downshift can also be induced by ad‐atoms with a different work function, because they can induce electron transfer from substrate metals (e. g. Pt) to them, lowering of density of states near Fermi level of the substrate metals to reach an equilibrium between two metals, [2,161] and this electron transfer can prevent the oxidation of substrate metals [40] . In addition, the lattice strain generated by ad‐atoms can also downshift the d‐band center of the metal they modify, and the effectiveness of lattice strain depends on the difference between their lattice parameters [162] .…”
Section: Electrocatalysts For Enhanced Efficiency and Selectivity Of mentioning
confidence: 99%
“…Both Carvalho and Muneeb groups used a simple reduction method for the synthesis process, borohydride metal ion reduction, and metal salt reduction. The catalyst particle size at equilibrium ratio from Carvalho et al 70 showed a slightly bigger particle size than Muneeb et al 86 However, both methods were found to be excellent in uniformly distributed the particles on the carbon support material with a low degree of agglomeration. Carvalho et al 85 found that Ni into Pd turned the catalyst into a segregation phase instead of an alloy state and the addition also caused the reversible formation of NiOOH from NiOH oxidation at high potential.…”
Section: Development Of Pt-based and Pdbased Catalyst With Nickel Metalmentioning
confidence: 87%
“…Carvalho et al, 85 Muneeb et al, 86 and Houache et al 87 explored multiple ratios of Pd/Ni for glycerol oxidation. Both Carvalho and Muneeb groups used a simple reduction method for the synthesis process, borohydride metal ion reduction, and metal salt reduction.…”
Section: Development Of Pt-based and Pdbased Catalyst With Nickel Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…For this concern, up to now a various combination of Pd based electrocatalysts including binary and ternary was developed and used for alcohol electro oxidations. Mostly Pd based bimetallic alloys are reported with Cu, Co, Ni, and, Ag, etc., for the electrocatalytic performances towards the various alcohols. Among other metals, according to oxo‐philic nature, Cu is considered more as a co‐catalyst or alloying with Pd.…”
Section: Introductionmentioning
confidence: 99%